Unravelling the effects of melt depletion and secondary infiltration on mantle Re-Os isotopes beneath the French Massif Central - Harvey, J; Gannoun, A; Burton, K; Schiano, P; Rogers, N; Alard, O (2010)
Spinel lherzolite xenoliths from Mont Briançon, French Massif Central, retain evidence for multiple episodes of melt depletion and melt/fluid infiltration (metasomatism). Evidence for primary melt depletion is still preserved in the co-variation of bulk-rock major elements (MgO 38.7-46.1 wt.%; CaO 0.9-3.6 wt.%), and many samples yield unradiogenic bulk-rock Os isotope ratios (187Os/188Os = 0.11541-0.12626). However, many individual xenoliths contain interstitial glasses and melt inclusions that are not in equilibrium with the major primary minerals. Incompatible trace element mass balance calculations demonstrate that metasomatic components comprise a significant proportion of the bulk-rock budget for these elements in some rocks, ranging to as much as 25% of Nd and 40% of Sr Critically, for Re-Os geochronology, melt/fluid infiltration is accompanied by the mobilisation of sulfide. Consequently, bulk-rock isotope measurements, whether using lithophile (e.g. Rb-Sr, Sm-Nd) or siderophile (Re-Os) based isotope systems, may only yield a perturbed and/or homogenised average of these multiple events. Osmium mass balance calculations demonstrate that bulk-rock Os in peridotite is dominated by contributions from two populations of sulfide grain: (i) interstitial, metasomatic sulfide with low [Os] and radiogenic 187Os/188Os, and (ii) primary sulfides with high [Os] and unradiogenic 187Os/188Os, which have been preserved within host silicate grains and shielded from interaction with transient melts and fluid. The latter can account for >97% of bulk-rock Os and preserve geochronological information of the melt from which they originally precipitated as an immiscible liquid. The Re-depletion model ages of individual primary sulfide grains preserve evidence for melt depletion beneath the Massif Central from at least 1.8 Gyr ago despite the more recent metasomatic event(s). © 2009 Elsevier Ltd. All rights reserved.